Formulation of empirical stiffness of folded beam - Lee, Wei Xiang. (2013)
Green technology is the way to go for the future. Harvesting energy from ambient energy provide infinite power unlike the battery. The objective was to obtain empirical mathematical model for the folded beam. To do this, influential parameters were obtained by the existing Euler Beam theory. The influential parameters were analyzed to understand how it affected the stiffness and stress of the whole folded beam. Empirical formulation based on objective model was fitted based on experimental data points to obtain the coefficients determined through curve fitting process such as least squares procedure. Empirical formulation of subsequent folds of the folded beam was also formulated the same way to obtain an empirical formula for the folded beam. Verification was also done with random designs to proof the accuracy of the empirical formula of the folded beam.